2021
DOI: 10.1002/jez.2531
|View full text |Cite
|
Sign up to set email alerts
|

Ecological adaptations of Amazonian fishes acquired during evolution under environmental variations in dissolved oxygen: A review of responses to hypoxia in fishes, featuring the hypoxia‐tolerantAstronotusspp.

Abstract: The Amazon Basin presents a dynamic regime of dissolved oxygen (DO) oscillations, which varies among habitats within the basin, including spatially, daily, and seasonally. Fish species inhabiting these environments have developed many physiological adaptations to deal with the frequent and periodic events of low (hypoxia), or no (anoxia) DO in the water. Cichlid fishes, especially the genus Astronotus (A. ocellatus and A. crassipinnis), are hypoxic‐tolerant species that can survive in very low DO levels for lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…Species greatly differ in their ability to survive in hypoxic conditions; aquatic organisms are no exception. A vast literature exists on hypoxia response in fish; in particular we have learned a great deal about adaptation to hypoxia from studies of hypoxia tolerant species (Braz‐Mota & Almeida‐Val, 2021; Mandic et al, 2018; Sloman et al, 2008; Somo et al, 2020; Zhou et al, 2020) and from comparison of transcriptional responses between hypoxia‐tolerant species and their more hypoxia‐sensitive relatives (Heinrichs‐Caldas & De Almeida‐Val, 2021; Lau et al, 2019; Mandic et al, 2014). Coherently with the data from terrestrial vertebrates reviewed above, studies reported decreased oxygen consumption, metabolic depression and, transcriptionally, upregulation of glycolysis and amino acid degradation pathways, oxidative‐stress‐related enzymes and pathways, such as mitogen‐activated protein kinase (MAPK) signaling pathway, and apoptotis‐related genes, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Species greatly differ in their ability to survive in hypoxic conditions; aquatic organisms are no exception. A vast literature exists on hypoxia response in fish; in particular we have learned a great deal about adaptation to hypoxia from studies of hypoxia tolerant species (Braz‐Mota & Almeida‐Val, 2021; Mandic et al, 2018; Sloman et al, 2008; Somo et al, 2020; Zhou et al, 2020) and from comparison of transcriptional responses between hypoxia‐tolerant species and their more hypoxia‐sensitive relatives (Heinrichs‐Caldas & De Almeida‐Val, 2021; Lau et al, 2019; Mandic et al, 2014). Coherently with the data from terrestrial vertebrates reviewed above, studies reported decreased oxygen consumption, metabolic depression and, transcriptionally, upregulation of glycolysis and amino acid degradation pathways, oxidative‐stress‐related enzymes and pathways, such as mitogen‐activated protein kinase (MAPK) signaling pathway, and apoptotis‐related genes, among others.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, pirarucus showed oscillations in lactate parameters at times AT and 48 h, and at time 48 h we observed a sudden drop in plasma lactate at a density of 195 g L À1 . In the literature, it is reported that Amazonian fish perform metabolic adjustments because of stressful situations, one of which is the increase in anaerobic metabolism with increased levels of plasma lactate (Braz-Mota & Almeida-Val, 2021). Exposure to stress results in increased lactate levels and altered oscillation, which is to be expected because the stress response results in the activation of mechanisms involved in nutrient supply over the time a stressor is present (Hernández-Pérez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current challenging conditions of particular water bodies, such as low pH, high temperature, and low dissolved oxygen, could be worsened by the ongoing climate changes. As many fish species already live near their physiological limits, environmental impacts on those water characteristics would impact the local aquatic biota (Braz-Mota and Almeida-Val 2021) This chapter will discuss the observed and predicted impacts of climate change in the Amazonian terrestrial and aquatic ecosystems. We will focus on the impacts on biodiversity, ecosystem services, carbon cycling, fisheries, and biomass burning emissions.…”
Section: Impacts Of Climate Change On Biodiversity Including Forest D...mentioning
confidence: 99%